Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1579/0044-7447-31.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Dynamics of Larval Populations of Anopheles messeae and A. atroparvus in the Delta of the Rivers Rhine and Meuse, The Netherlands

Abstract: The distribution and ecology of mosquitoes of the Anopheles maculipennis complex were studied in the delta of the rivers Rhine and Meuse in the southwest of The Netherlands. The study area was previously malarious, with A. atroparvus being the only vector. 125 potential aquatic habitats of A. maculipennis were sampled, of which 47 (37.6%) contained larvae of this species complex. Larval densities varied from 7.4-325.93 larvae m-2. There was no correlation between chlorinity (@1000) of the water and presence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 7 publications
1
31
0
Order By: Relevance
“…messeae are typically found in shaded, clear, very slow flowing or stagnant, fresh water sites [230,262-264] such as lake margins and marshes [263-265]. Despite only sampling resting females, Adamovic, in Serbia and Montenegro [266-268] and Adamovic & Paulus [269], in surveys of Slovenia and Croatia, continually associated the presence of adult An.…”
Section: Resultsmentioning
confidence: 99%
“…messeae are typically found in shaded, clear, very slow flowing or stagnant, fresh water sites [230,262-264] such as lake margins and marshes [263-265]. Despite only sampling resting females, Adamovic, in Serbia and Montenegro [266-268] and Adamovic & Paulus [269], in surveys of Slovenia and Croatia, continually associated the presence of adult An.…”
Section: Resultsmentioning
confidence: 99%
“…A. claviger has also locally been reported as a vector [15]. Some recent research, however, has questioned A. messeae as a vector of malaria [36]. Jaenson & Ameneshewa [37] reported that blood-feeding was not a prerequisite for hibernation of A. messeae .…”
Section: Resultsmentioning
confidence: 99%
“…These mosquitoes were transported to the Laboratory of Entomology of Wageningen University for species identification. The Bender buffer method [39] was used to extract DNA from a mosquito leg and part of the abdomen of each mosquito, followed by polymerase chain reaction (PCR) analysis [40]. …”
Section: Methodsmentioning
confidence: 99%